2005
DOI: 10.1128/iai.73.7.4309-4314.2005
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Intestinal Alkaline Phosphatase Attenuates the Inflammatory Response in Secondary Peritonitis in Mice

Abstract: Lipopolysaccharide (LPS) contributes importantly to morbidity and mortality in sepsis. Bovine intestinal alkaline phosphatase (BIAP) was demonstrated to detoxify LPS through dephosphorylation. LPS injection combined with BIAP reduced inflammation and improved survival in various experimental settings. In this study, single-dose intravenous administration of BIAP (0.15 IU/g) was applied in a murine cecal ligation and puncture (CLP) model of polymicrobial sepsis. Saline was given as control (S group). Treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 30 publications
3
51
1
Order By: Relevance
“…Pharmacologically, IAP has been found to be an effective therapy against various human as well as animal disease models including IBD, necrotizing enterocolitis, gram-negative sepsis, C. difficile, and S. typhimurium infections, and metabolic syndrome (1,21,34,44,56,58,61). Clinical trials using bovine IAP against colitis have shown that IAP has no or minimal side effects (34).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacologically, IAP has been found to be an effective therapy against various human as well as animal disease models including IBD, necrotizing enterocolitis, gram-negative sepsis, C. difficile, and S. typhimurium infections, and metabolic syndrome (1,21,34,44,56,58,61). Clinical trials using bovine IAP against colitis have shown that IAP has no or minimal side effects (34).…”
Section: Discussionmentioning
confidence: 99%
“…Recently there has been renewed interest in IAP activity and its role in promoting intestinal mucosal defense (15). Several studies have shown that LPS dephosphorylation mediated by IAP protects the host against LPS-induced inflammation as well as reducing the systemic translocation of enteric bacteria (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). To investigate whether IAP activity was playing a role in the increased susceptibility/morbidity of Muc2 Ϫ/Ϫ mice in our model, we stained for IAP and found that Muc2 Ϫ/Ϫ mice had reduced IAP expression as well as reduced LPS dephosphorylation activity (a measure of the activity of IAP) within their cecal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IAP-mediated LPS detoxification plays a role in preventing systemic translocation of LPS across the intestinal barrier (15)(16)(17)(18)(19)(20)(21). In the absence of this detoxification, systemic translocation of LPS triggers exaggerated inflammatory responses that can ultimately prove fatal to the host through proinflammatory cytokine-induced septic shock (22,23,24).…”
mentioning
confidence: 99%
“…In previous animal studies, promising therapeutic effects have been shown in reducing the inflammatory response with the use of intravenous alkaline phosphatase (9)(10)(11). In a clinical study in severe sepsis patients, continuous infusion of calf-intestinal alkaline phosphatase significantly improved renal function (12,13).…”
Section: Methodsmentioning
confidence: 98%